Digital Pathways to Integration: Social Media Use by African Immigrants in Hungary - (:unkn) unknown (My University, 2025)
Social media is pivotal in sharing updates on migration and integration-related news. Multiple platforms such as Facebook and WhatsApp have gathered a lot of attention from immigrant communities that attempt to distribute vital information surrounding legal and bureaucratic affairs in their host country. On that note, this study explores how African immigrants in Hungary utilize social media to navigate challenges within a new social environment. Thanks to focus groups conducted in Budapest with the participation of immigrants with diverse backgrounds during the first quarter of 2025, the study also aims to identify the particularities regarding information accessibility and information-seeking behaviors. Initial results from the qualitative analysis of the field research indicate that differences in social media usage depend on the ties of the countries of origin with European states that used to be colonial powers. At the same time, it is evident that immigrants with linguistic and cultural backgrounds from North Africa share more similarities with the Arab-speaking communities than those with a homeland from Central or Eastern Africa. Among others, personal experiences vary because of several factors, namely period spent in Hungary and relatives or friends residing in the same country. Additionally, dominant narratives require a more thorough analysis by including ethnicgroups worldwide. Ultimately, the research findings from this study can be the foundation for tracking migrant behaviors in a sociopolitical context governed by an anti-migration agenda. The latter unveils a nuanced perspective on media discourse by embedding sociocultural anthropology to address complexities in the Hungarian society.
Keywords: African Research